Visualising slavery art across the African diaspora - Bernier, Celeste-Marie 1975-; Durkin, Hannah ca. 20./21. Jh (Liverpool University Press, 2021)
The purpose of this book is to excavate and recover a wealth of under-examined artworks and research materials directly to interrogate, debate and analyse the tangled skeins undergirding visual representations of transatlantic slavery across the Black diaspora. Living and working on both sides of the Atlantic, as these scholars, curators and practitioners demonstrate, African diasporic artists adopt radical and revisionist practices by which to confront the difficult aesthetic and political realities surrounding the social and cultural legacies let alone national and mythical memories of Transatlantic Slavery and the international Slave Trade. Adopting a comparative perspective, this book investigates the diverse body of works produced by black artists as these contributors come to grips with the ways in which their neglected and repeatedly unexamined similarities and differences bear witness to the existence of an African diasporic visual arts tradition. As in-depth investigations into the diverse resistance strategies at work within these artists' vast bodies of work testify, theirs is an ongoing fight for the right to art for art's sake as they challenge mainstream tendencies towards examining their works solely for their sociological and political dimensions. This book adopts a cross- cultural perspective to draw together artists, curators, academics, and public researchers in order to provide an interdisciplinary examination into the eclectic and experimental oeuvre produced by black artists working within the United States, the United Kingdom and across the African diaspora. The overall aim of this book is to re-examine complex yet under-researched theoretical paradigms vis-a-vis the patterns of influence and cross-cultural exchange across both America and a black diasporic visual arts tradition, a vastly neglected field of study
"Visualising Slavery: Art Across the African Diaspora is the result of an international symposium generously funded by the Terra Foundation for American Art and held at the University of Oxford in 2013" - Seite xv
Keywords: Geschichte 1700-2010; Slavery in art; Slave trade in art; African diaspora in art; Künste; Sklaverei -- Motiv; Afrika; Konferenzschrift -- 2013 -- Oxford